Sustainable soil fertility management in coconut based multi-storeyed cropping system - A.S. Anilkumar, P. Farsanashamin and (Journal of Plantation Crops, 2016)
A field experiment was conducted at College of Agriculture, Padannakkad, Kasaragod, Kerala state during 2012 to 2015 to develop appropriate cost effective practices for enhancing productivity and profitability of coconut based multi-storeyed cropping system involving a combination of coconut, noni, banana and long pepper in coastal sandy soil. The treatments consisted of eight combinations of four levels of NPK (100 per cent, 2/3 rd, 1/3 of the recommended NPK and basin management in the organic pathway) for coconut and two levels of NPK (100 and 75 per cent of the recommended dose) for the component crops in addition to five sole cropping systems namely, coconut (100 per cent NPK), coconut (organic), long pepper (100 per cent NPK), banana (100 per cent NPK) and noni (100 per cent NPK). Pooled analysis of the data revealed that basin management with 75 per cent NPK for component crops was found favourable for increasing the nut yield from 43 to 53 nuts palm-1 year-1. Soil properties and BCR of the system also improved as a result of the same treatment. Highest copra content (160.6 g nut-1) was recorded in the organic basin management treatment supplied with 100 per cent NPK for component crops. An improvement in the soil nutrient status was also observed compared to the control.